Screening of Genes Related to Growth, Development and Meat Quality of Sahan Crossbred F1 Sheep Based on RNA-Seq Technology - Song, Yali; Zhang, Quanwei; Shi, Jinping; Fu, Lingjuan; Cheng, Shuru (Frontiers in Veterinary Science, 2022)
This study aimed to identify genes related to sheep growth, development and meat quality. Small-tailed Han sheep (STH), and small-tailed Han sheep and Suffolk hybrid F1 (STH×SFK), were selected to determine the growth performance, slaughter performance, and meat quality. The longissimus dorsi muscle was selected for transcriptome sequencing, and the target gene was screened based on bioinformatics analysis; real-time fluorescent quantitative PCR (RT-PCR) and western blotting (WB) were conducted to verify the target gene. Locations of genes in tissues were confirmed via immunofluorescence. The results showed that the pre-slaughter live weight, bust circumference, slaughter performance, and marbling score of the STH×SFK population were significantly higher than those of the STH population (P<0.01). Sequencing results showed that 560 differentially expressed genes (DEGs) were identified in the STH×SFK population, of which 377 exhibited upregulated and 183 exhibited downregulated expression levels. GO annotation revealed that differentially expressed genes could be classified into 13 cell components, 10 molecular functions, and 22 biological processes. The KEGG enrichment analysis showed that DEGs were mainly enriched in the Rap1 signaling pathway, Ras signaling pathway, and other pathways related to growth and meat quality. Based on the GO and KEGG analyses, four candidate genes related to sheep growth and meat quality, namely myostain (MSTN), interferon-related developmental regulator 1 (IFRD1), peroxisome proliferator activator receptor delta (PPARD), and myosin light chain 2 (MLC2 or MYL2), were screened. The expression levels of genes and proteins were verified via RT-PCR and WB, and the results were consistent with the trend of transcriptome sequencing. Immunofluorescence results showed that IFRD1 was expressed in the cytoplasm and nucleus, and MYL2 was expressed in the cytoplasm. This study revealed the mechanism of gene regulation of sheep growth and development at the molecular level and provided a theoretical basis for studying sheep genetics and breeding.